Designing Junior Sport to Maximize Potential: The Knowns, Unknowns, and Paradoxes of Scaling Sport - Buszard, Tim; Farrow, Damian; Reid, Machar (Frontiers in Psychology, 2020)
In this mini-review we draw attention to an important yet relatively untapped topic in the developmental pathway – the design of junior sport so that it appropriately matches the functional capacities of children. Junior sport is a regular weekend activity for many children across the world, yet many will be required to prematurely play on a field or with equipment that is designed for adults. Herein lies an opportunity for sport administrators to nurture children’s development in sport by appropriately manipulating the rules and dimensions of the game. The aim of this mini-review is to (a) draw attention to the value of scaling junior sport, (b) highlight paradoxes within the current scaling sport literature, and (c) emphasise a way forward for junior sport research. If we are genuine in our endeavour to tailor sports experiences for children, more sophisticated approaches to scaling those experiences are a must.